2009
DOI: 10.1002/aic.11710
|View full text |Cite
|
Sign up to set email alerts
|

Performance features of Pt/BaO lean NOx trap with hydrogen as reductant

Abstract: in Wiley InterScience (www.interscience.wiley.com).The performance of a model Pt/BaO/Al 2 O 3 monolith catalyst was studied using H 2 as the reductant. The dependence of product selectivities on operating parameters is reported, including the durations of regeneration and storage times, feed composition and temperature, and monolith temperature. The data are explained in terms of a phenomenological model factoring in the transport, kinetic, and spatio-temporal effects. The Pt/BaO catalyst exhibits high cycle-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
7
31
0
Order By: Relevance
“…9b). This agrees with the observation of Clayton et al [91] that nitrogen selectivity increased with the NOx/H2 ratio.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…9b). This agrees with the observation of Clayton et al [91] that nitrogen selectivity increased with the NOx/H2 ratio.…”
supporting
confidence: 93%
“…The hydrogen concentration influences significantly the formation of ammonia at the exit, from 15 ppm NH3 for 0.79% H2 to a maximum of 300 ppm NH3 for 2.32% H2. In fact, the higher H2 concentration in the reduction stream the higher NH3 concentration at the exit, as previously reported [56,78,[87][88][89]91]. These experiments also confirmed the delay in the ammonia detection at the reactor exit related to the beginning of the rich period, as it was observed in the experiments of section 3.…”
Section: Effect Of the H2 Concentration In The Regeneration Stream Onsupporting
confidence: 79%
See 1 more Smart Citation
“…At variance, N 2 O is a highly undesired by-product in view of its very high global warming potential (nearly 300 times that of CO 2 ). Over fully formulated catalysts, it has been shown that N 2 O formation is apparent both upon switch from lean to rich mode but also during the alternation from rich to lean regime [3][4][5][6][7][8]. It has been suggested that N 2 O formation at the lean to rich transition occurs at the regeneration front, upon reduction of the stored NO x over not fully reduced Platinum-Group-Metal (PGM) sites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the engine is operated in rich mode for a few seconds, in order to remove the stored NO x from the catalyst's surface and subsequently to reduce the released NO x mainly into N 2 and secondarily into N 2 O and NH 3 . The interested reader may find in the literature several experimental studies on the performance of the NSR catalyst as well as simulation studies and kinetic models …”
Section: Introductionmentioning
confidence: 99%